Space-borne GNSS radio occultation: validation and analysis of the observed tropopause over South America - NASCIMENTO, Absalão Aranha (2019)
Global and regional tropopause monitoring (temperature and height) has taking advantage of atmospheric remote sensing using Global Navigation Satellite System - Radio Occultation (GNSS-RO). In this study, 622,914 GNSS-RO data observations obtained by CHAMP (Challenging Minisatellite Payload), GRACE (Gravity Recovery and Climate Experiment) and COSMIC (Constellation Observing System for Meteorology Ionosphere & Climate), considering 200 months (2001 to 2017) were used to analyze the variability of the height and temperature of the Lapse-Rate Tropopause (LRT) over South America. Firstly the atmospheric profiles were validated using atmospheric observations for 54 radiosonde stations. The results considering South America showed a new trend of 13.450 ± 0.677 meters per decade for the tropopause height which indicates a regional tropopause increase and a corresponding temperature decrease of -0.021 ± 0.002K per decade. The PCA (Principal Component Analysis) of the anomalies of temperature and height of the tropopause presented a significant correlation of 0.60 of the variability of the tropopause with the ENSO (El Niño–Southern Oscillation) phenomenon. The detected increase of tropopause height in South America revel warming evidence that should be monitored.